The determinants of institutionalization of Zakāt: The~case of Morocco - Hafssa Yerrou; Amina Achmaoui; Oumaima Bezoui (Islamic Economic Studies (IES), 2023)
Purpose - Muslims have several religious obligations; the payment of a defined sum to the deprived part of the society is one of their financial obligations called Zakat. The institutionalization of this obligation has been the focal point of several research studies, however the Moroccan context has been studied by very few researchers. Therefore, this research aims to study the institutionalization of Zakat in the Moroccan context. Design/methodology/approach - In this paper, the authors try to drive focus to the determinants of the payment of Zakat to a specialized institution in Morocco (institutions whose main activity is the management of zakat funds), through 302 questionnaires that have been administrated on Moroccans and partial least square (PLS) approach. Findings - The results show that the intention and payment behavior of Zakat by Moroccans depends on the quality of the zakat institution's quality of services, its location, the competence and availability of personnel, the use of technology, the shari'ah compliance of the institution's activities and the trust by showing professionalism in the management of Zakat funds and disclose information. Research limitations/implications - The lack of relevant data covering the number of Zakat payers in Morocco, their potential contributions and the amounts paid each year, slows down the progress of this project as it hinders the ability of state officials and decision-makers to assess the potential zakat funds that are currently in circulation, and thus makes it hard for them to attribute financial support to such project. It also makes it hard for researchers to get direct access to Muzzakis. Practical implications - The existing literature shows immense interest in the implementation of institutions who can manage the Islamic social instruments especially zakat. However, the lack of relevant payer data of Zakat in Morocco and other jurisdictions who have not yet institutionalized zakat slows down the progress of this project and hinders any progress. Thus, the initiating point of such institutions in Morocco and in other countries who have not yet launched this project, requires knowing what determines the behaviour of Zakat payers and their choice of paying zakat to an institution. The results of our research help give insights on the determinants of zakat institutionalization from zakat payers point of view. These results are useful to the state policy makers. Social implications - Like other neighboring countries, Morocco must introduce Zakat into its social system in order to better manage the funds that will enable the tackling of serious social problems such as poverty. Originality/value - In contrast to the widespread and extensive literature available in analyzing the determinants of donations and volunteering from a conventional perspective, the parallel analysis of these same concerns in social Islamic systems is still in its infancy and so is the implementation of institutions related to zakat and other traditional Islamic social instruments such as waqf.
Keywords: E14; E15; 330; Determinants; Institutionalization; PLS; Theory of planned behavior; Zakāt